CONVERSATIONS -- AND NEGOTIATED INTERACTION -- IN TEXT AND VOICE CHAT ROOMS - Kevin Jepson (Language Learning and Technology)
Despite the expanded use of the Internet for language learning and practice, little attention if any has been given to the quality of interaction among English L2 speakers in conversational text or voice chat rooms. This study explored the patterns of repair moves in synchronous non-native speaker (NNS) text chat rooms in comparison to voice chat rooms on the Internet. The following questions were posed: (a) Which types of repair moves occur in text and voice chats; and (b) what are the differences, if any, between the repair moves in text chats and voice chats when time is held constant? Repair moves made by anonymous NNSs in 10, 5-minute, synchronous chat room sessions (5 text-chat sessions, 5 voice-chat sessions) were counted and analyzed using chi-square with alpha set at .05. Significant differences were found between the higher number of total repair moves made in voice chats and the smaller number in text chats. Qualitative data analysis showed that repair work in voice chats was often pronunciation-related. The study includes discussion that may affect teachers' and learners' considerations of the value of NNS chat room interaction for second language development.